Tata Kelola Kolaboratif dalam Pengelolaan Sampah Plastik: Studi Kasus di Kabupaten Lamongan - Wartono, Wartono; Erison, Yendra; Rohmah, Eva Nur Laily (Sahabat Akademia Group, 2025)
The problem of plastic waste is a crucial issue facing many regions, including Lamongan Regency, which experiences a significant increase in waste volume each year. Despite management programs, such as